Corporate Communication through the Campaign of Consuming Jamu - Roosinda, Fitria Widiyani (Jurnal The Messenger, 2021)
This research is motivated by the phenomenon of increasing consumption of empon-empon products by the community since the emergence of the Covid-19 pandemic in Indonesia. Empon-empon is ones of jamu (traditional herbal drink) which the ingredients is consisting of ginger, turmeric and other spices. The community believes that empon-empon is able to prevent from Covid-19. This contributes to build simultaneous awareness of the community and ultimately creates a lifestyle of consuming jamu. This situation is used by jamu corporate (Jamu Iboe) to conduct campaigns to drink jamu to increase sales of their products. This study aims to determine the campaign strategy for drinking jamu, how the community responds to the campaign, and what jamu products are most in demand. Qualitative descriptive is the method used in this research by conducting in-depth interviews. This research concludes that jamu corporates carry out their corporate communication program strategies through social media by inviting people to drink jamu and unite to prevent and fight Covid-19. The public response to jamu is very high, compared to before the pandemic. The most popular herbs are ginger, white turmeric, temulawak and sambiloto.